ALGORITMA NEURAL NETWORK UNTUK PREDIKSI PENYAKIT JANTUNG - Bakhtiar Rifai (Jurnal Techno Nusa Mandiri, 2013)
Heart disease is the occurrence of partial or total blockage of a blood vessel over, as a result of the self blockage deep chemical energy supply to the heart muscle is reduced, resulting in an impaired balance between supply and in predicting heart disease have been carried out by several previous investigators. In this study will be done for heart disease prediction algorithm using a neural network and improved the performance of the neural network algorithm is implemented on the data of heart disease patients. From the test results by measuring method using a neural network based, it is known that neural network algorithms yield accuracy values 91.45%, precision 92.79 %, recall 94.27% and AUC values obtained 0.937. by looking at the accuracy, the algorithm based neural network into the category of groups is very good, because of AUC values between 0.90 – 1.00.